Circular RNA circMYBPC1 promotes skeletal muscle differentiation by targeting MyHC - Mengjie Chen; Xuefeng Wei; Mingming Song; Rui Jiang; Kongwei Huang; Yanfei Deng; Qingyou Liu; Deshun Shi; Hui Li (Elsevier, 2021)
Skeletal muscle development is a complex and highly orchestrated biological process mediated by a series of myogenesis regulatory factors. Numerous studies have demonstrated that circular RNAs (circRNAs) are involved in muscle differentiation, but the exact molecular mechanisms involved remain unclear. Here, we analyzed the expression of circRNAs at the adult and embryo development stages of cattle musculus longissimus. A stringent set of 1,318 circRNAs candidates were identified, and we found that 495 circRNAs were differentially expressed between embryonic and adult tissue libraries. We subsequently focused on one of the most downregulated circRNAs (using the adult stage expression as control), and this was named muscle differentiation-associated circular RNA (circMYBPC1). With RNA binding protein immunoprecipitation (RIP) and RNA pull-down assays, circMYBPC1 was identified to promote myoblast differentiation by directly binding miR-23a to relieve its inhibition on myosin heavy chain (MyHC). In addition, RIP assays demonstrated that circMYBPC1 could directly bind MyHC protein. In vivo observations also suggested that circMYBPC1 may stimulate skeletal muscle regeneration after muscle damage. These results revealed that the novel non-coding circRNA circMYBPC1 promotes differentiation of myoblasts and may promote skeletal muscle regeneration. Our results provided a basis for in-depth analysis of the role of circRNA in myogenesis and muscle diseases.